Implementation of the Agricultural-Based Independent Village Program in Biroro Village, East Sinjai District, Sinjai Regency - Jamaluddin Jamaluddin; Suardi Mukhlis; Syahril Syahril; Sutra Sutra (Jurnal Office, 2021)
The work program of the central government is of course also a program for the Regional Government. This is a reference for the government in Biroro Village, East Sinjai District, Sinjai Regency, South Sulawesi Province at this time in realizing and implementing development programs that have been set by the Biroro Village Government. This study aims to determine the implementation of the Agriculture-Based Independent Village Program in Biroro Village, East Sinjai District, Sinjai Regency. The type of research is qualitative, where the data collection techniques are observation, interviews and documentation. The informants consisted of the Head of Biroro Village, Agricultural Extension Center, Village Government Officials, Biroro Village BPD, and Gapoktan (Farmers Group Association). Data analysis techniques were carried out by means of data reduction, data presentation and conclusions. Based on the results of the study, that communication in the implementation of the Agriculture-Based Independent Village Development Program between the Village Government and community leaders, as well as farmer group institutions in the implementation of the Agriculture-Based Independent Village Program has been well established, where the Village Government involves the entire community so that they can participate in every activity. implementation of development programs